Performance management and policy evaluation of information and communication technology graduate program for developing countries - Kang, Dongsuk; Park, Min Jae (Evaluation and Program Planning, 2024)
As an educational aid, the Korean government has developed and funded a graduate-level global information telecommunications technology program (ITTP) for ICT officers in developing countries. Questions have arisen about whether the program can achieve its goals and obtain mutual benefits between Korea and participating nations. Using a total quality management (TQM) framework as a unique case analysis, we evaluated ITTP's resources and performance from 2006 to 2014. Our results show that ITTP has focused on the quantitative promotion of students and alums from various countries and their learning of Korea-centric ICT, policies, and culture. In particular, the Korean government's lax evaluation of ITTP performance has led to weak responsibility, ambiguous task identity, missed opportunities for self-improvement, and low participation among students and stakeholders. These findings highlight the need for graduate programs and their stakeholders to reinforce internal and external evaluations of the program's performance and provide feedback for reciprocal development.
Keywords: Communication; Developing Countries; Humans; Program Evaluation; Public Policy; Technology; Asia; Educational management; Higher education; Program identity; Technical aid